Standardized test for anti-Tr/DNER in patients with paraneoplastic cerebellar degeneration - Probst, Christian; Komorowski, Lars; de Graaff, Esther; van Coevorden-Hameete, Marleen; Rogemond, Veronique; Honnorat, Jerome; Sabeter, Lidia; Graus, Francesc; Jarius, Sven; Voltz, Raymond; Wildemann, Brigitte; Franciotta, Diego; et al. (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2015)
Objective: To determine sensitivity and specificity of a standardized recombinant cell-based indirect immunofluorescence assay (RC-IFA) for anti-Tr antibodies in comparison to a reference procedure. - Methods: Delta/Notch-like epidermal growth factor-related receptor (DNER) was expressed in HEK293 and used as a substrate for RC-IFA. HEK293 control cells expressing CDR2/Yo and CDR2L as well as mock-transfected HEK293 cells were used as controls. Serum samples from 38 patients with anti-Tr antibodies (33 with paraneoplastic cerebellar degeneration [PCD] and Hodgkin lymphoma), 66 patients with anti-Tr-negative PCD, 53 patients with Hodgkin lymphoma without neurologic symptoms, 40 patients with rheumatic diseases, and 42 healthy blood donors were tested for anti-DNER reactivity in the RC-IFA. In addition, RC-IFA results were compared to those from a commercial tissue-based IFA using monkey cerebellum. - Results: Using the RC-IFA, anti-DNER was detected in all anti-Tr-positive patients but in none of the controls (sensitivity 100%, 95% confidence interval [CI] 92.8%-100%; specificity 100%, 95% CI 98.7%-100%). In comparison, anti-Tr was not detected in 4 samples with low-titer autoantibodies using the commercial tissue-based assay. Preadsorption of sera with either recombinant full-length DNER or its extracellular domain selectively abolished anti-Tr reactivity. - Conclusion: Anti-Tr antibodies bind to the extracellular domain of DNER and can be detected by RC-IFA using HEK293 cells expressing the recombinant receptor. The new method performs better than a frequently used commercial tissue-based indirect immunofluorescence assay (IFA) in samples with low-titer antibodies.
Gesehen am 22.07.2020